The Economic Content of Indicators of Developing Country Creditworthiness. (IMF Working Papers; Working Paper ;, 1996)
This paper analyzes the economic determinants of developing country creditworthiness indicators for over 60 developing countries for the period from 1980 to 1993. Our results indicate that economic fundamentals--the ratio of non-gold foreign exchange reserves to imports, the ratio of the current account balance to GDP, growth, and inflation explain a large amount of the variation in the credit ratings. All developing country ratings were adversely affected by an increase in international interest rates independently of the domestic economic fundamentals. A country's regional location and the structure of its exports (such as whether it is primarily an exporter of fuel products or manufactured products) were also important.